Pollen-food syndrome in the adolescent - Pita, Joana Sofia (2019)
Pollen-food syndrome (PFS) is characterized by allergic symptoms elicited by the ingestion of raw fruits or vegetables in patients with seasonal allergic rhinitis/rhinoconjunctivitis. The estimated prevalence of PFS in patients with pollen allergy is 50–70%. Typically, PFS-induced symptoms are restricted to the oral cavity (oral allergy syndrome – OAS). The authors present the case of a female adolescent with grass pollen allergic rhinitis treated with oral immunotherapy for four years and four months, who developed OAS to fresh fruits and walnuts. Diagnostic workup showed sensitization to several allergens, particularly to profilin, which seems to be responsible for PFS. The patient remains asymptomatic with fresh fruits and walnut avoidance, currently tolerating cooked apple, without symptoms.